Effect of oxygen concentration and external radiation on the thermal decomposition and combustion characteristics of electric wire - Yanli, Zhao; Xuelin, Zhang; Shengfeng, Luo; Xiaoliang, Zhang (Journal of thermal analysis and calorimetry, 2022)
The aim of this study is to investigate the thermal decomposition and combustion characteristics of electric wire under different oxygen concentrations and external radiations. Fire propagation apparatus was used, and the thermal decomposition, limit oxygen concentration, ignition time, mass loss rate, and heat release rate are discussed. It was found that under nitrogen atmosphere, higher external heat flux promoted the thermal decomposition. The mass loss rate of decomposition exhibited a linear behavior versus radiant heat flux. The limit oxygen concentration was linearly reduced with increasing external heat flux. For the combustion process, the ignition time decreased while the mass loss rate increased with the increasing oxygen concentration and external heat flux. The wire sample used in this study is proved to be thermally thin and the increase rate of the mass loss rate reduced under high external heat flux. The peak heat release rate increases with oxygen concentration under low external heat flux. While under high external heat flux, the peak heat release rate first increaseed and then decreaseed with oxygen concentration due to the effect of increasing heat blockage effect.